Metal-ligand cooperativity in iron dinitrogen complexes: proton-coupled electron transfer disproportionation and an anionic Fe(0)N2 hydride - Regenauer, Nicolas I.; Wadepohl, Hubert; Roşca, Dragoş-Adrian (Inorganic chemistry, 2022)
Metal-ligand cooperativity and redox-active ligands enable the use of open-shell first-row transition metals in catalysis. However, the fleeting nature of the reactive intermediates prevents direct inspection of the relevant catalytic species. By employing phosphine α-iminopyridine (PNN)-based complexes, we show that chemical and redox metal-ligand cooperativity can be combined in the coordination sphere of iron dinitrogen complexes. These systems show dual activation modes either through deprotonation, which triggers reversible core dearomatization, or through reversibly accepting one electron by reducing the imine functionality. (PNN)Fe(N2) fragments can be obtained under mildly reducing conditions. Deprotonation of such complexes induces dearomatization of the pyridine core while retaining a terminally coordinated N2 ligand. This species is nevertheless stable in solution only below −30 °C and undergoes unusual ligand-assisted redox disproportionation through proton-coupled electron transfer at room temperature. The origin of this phenomenon is the significant lability of the α-imine C-H bonds in the dearomatized species, where the calculated bond dissociation free energy is 48.7 kcal mol-1. The dispropotionation reaction yields an overreduced iron compound, demonstrating that the formation of such species can be triggered by mild bases, and does not require harsh reducing agents. Reaction of the dearomatized species with dihydrogen yields a rare anionic Fe hydride that binds dinitrogen and features a rearomatized core.